SURGICAL TREATMENT OF PATIENTS WITH ACUTE SIGMOID OBSTRUCTION - Khodjimatov Gulomidin Minkhodzhievich; Khakimov Dilshodbek Mamadalievich; Khamdamov Khabibullo Khamdamovich; Mamadiev Azizbek Maribjanovich; Karaboev Bekzodbek Bakhodirovich; Kasimov Nosirbek Adkhamovich (Scholar Express Journals, 2022)
Progress in gastrointestinal surgery associated with the use of powerful antibiotics, new suture materials, and hardware formation of interintestinal anastomoses has not solved the problem of intestinal wall suture failure. Today in gastrointestinal surgery, single-row intestinal suture without mucosal traumatization has become widespread as in recent years many researches have proved an important role of intestinal mucosa in tissue regeneration of gastrointestinal anastomosis zone [2, 3, 6, 7].
Keywords: Gastro-Intestinal Tract; Surgical Treatment; Acute Sigmoid Obstruction